2014
DOI: 10.1002/bies.201400036
|View full text |Cite
|
Sign up to set email alerts
|

Spurious transcription factor binding: Non‐functional or genetically redundant?

Abstract: Transcription factor binding sites (TFBSs) on the DNA are generally accepted as the key nodes of gene control. However, the multitudes of TFBSs identified in genome-wide studies, some of them seemingly unconstrained in evolution, have prompted the view that in many cases TF binding may serve no biological function. Yet, insights from transcriptional biochemistry, population genetics and functional genomics suggest that rather than segregating into ‘functional’ or ‘non-functional’, TFBS inputs to their target g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 119 publications
2
74
0
Order By: Relevance
“…When expression of TRP32 targets was examined, we found that 80% were differentially regulated during infection. This is an expected result, as transcription factors typically bind many nonfunctional sites, with reports of as many as ϳ50 to 99.9% of transcription factor-bound sites not having a clear functional role (42,43). Most gene targets showed differences in expression primarily at 72 hpi, although some showed changes at 48 hpi as well.…”
Section: Discussionmentioning
confidence: 65%
“…When expression of TRP32 targets was examined, we found that 80% were differentially regulated during infection. This is an expected result, as transcription factors typically bind many nonfunctional sites, with reports of as many as ϳ50 to 99.9% of transcription factor-bound sites not having a clear functional role (42,43). Most gene targets showed differences in expression primarily at 72 hpi, although some showed changes at 48 hpi as well.…”
Section: Discussionmentioning
confidence: 65%
“…Alternatively, these sequences may be subject to spurious regulatory activity, which would explain the findings that: (1) only a minority of genetically variable TF-DNA binding events result in differential gene expression (this work), (2) a large portion of TF-DNA binding events have no functional consequence (Cusanovich et al, 2014;Farnham, 2009), and (3) TF binding sites tend to experience rapid turnover (Dermitzakis and Clark, 2002;Villar et al, 2015). Another complementary interpretation involves the model of dose-dependent gene activation in which several TF binding sites in multiple elements cumulatively contribute to gene expression (Spivakov, 2014). Under this model, loss of TF-DNA binding at one binding site would have little to no discernible functional consequence as long as the other implicated TF binding sites remain intact.…”
Section: Discussionmentioning
confidence: 83%
“…Yet, the very same genes are dependent on T-bet in immature NK cells, at a stage where Zeb2 is expressed at low and ineffective levels. This suggests that both TFs contribute to transcriptional activation in a cumulative rather than synergistic fashion, a notion arising from the analysis of genome-wide studies (Spivakov, 2014). Other TFs may also cooperate with T-bet and Zeb2 to confer robustness to the regulatory network as Zeb2 is known to recruit several transcriptional cofactors (Conidi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%